(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper focused on Aging and Modernization A focus of social Culture Change. The main objective of research paper is to study the social Culture profile of the elderly in Agra city and the effect of modernization of the elderly in Agra city we also study the relationship between modernization and problems of the elderly in Agra city. Our sample size is 40 Elderly in Agra city. For the purpose of data collection A structured interview schedule was used to collect the data on their social Cultural information, effect of modernization of the elderly.The data was calculated using the percentage method. The major finding was themain problems of the elderly are social change, Culture change, modernization.The Traditional Indian social system has been changing very fast because of the steadily engulfing forces of modernization, urbanization, industrialization and other such processes. It has drastically affected theNuclear Family System, Western Lifestyle, Communication (Both Generations), Adjustment in younger with elders papule in family, moral value, More Job opportunities, More Job and business field, Cast system, Health facilities,Industrialization Economicalchange, Financial Security, Social Security, Psychological Change etc some of the positive change and some of the negative change in society but all are affect the elder life.